Congruences on regular semigroups with Q-inverse transversals - Wang, A.; Wang, L. (Ukrains’kyi Matematychnyi Zhurnal, 2016)
We give congruences on a regular semigroup with a Q-inverse transversal S^o by the congruence pair (abstractly), which consists of congruences on the structural component parts R and Λ. We prove that the set of all congruences for this kind of semigroups is a complete lattice.